Pengaruh Penerapan Bauran Pemasaran Terhadap Loyalitas Konsumen Goro Assalam Hypermarket Surakarta - Hidayanto, Febri, Ahmad Mardalis, SE.,MBA (2016)
This study aimed to determine the level of influence the application of marketing mix of product, price, place, promotion, people, physical evidence and process customer loyalty Goro Assalam Hypermarket Surakarta. The sampling method is based on convenience sampling technique, where samples are selected with consideration of ease and in accordance with the criteria of the study, which the authors gave questionnaires to respondents in the meet specific criteria. The results showed that in partial product, promotion, place, physical evidence and process a significant effect on consumer loyalty Goro Assalam Hypermarket, while variable rates and no significant effect on consumer loyalty Goro Assalam Hypermarket. Simultaneously the product, price, promotion, place, people, physical evidence and process a significant effect on consumer loyalty Goro Assalam Hypermarket. Given the price and people variable has no significant effect on consumer loyalty Goro Assalam Hypermarket, then management need to correct again the role of price and people variable in marketing planning company subsequent.